Analisis Analisis Dialog Persuasif Mu'min Dengan Fir'aun Dalam Tafsir Sayyid Quthb - yovia_violanda Fransiska; Jani Arni; Wilaela Wilaela; Dasman Yahya Ma’ali (LPPM Sekolah Tinggi Ilmu Al-Qur'an Wali Songo Situbondo, 2026)
The persuasive communication used by Mu'min in his dialogue with Pharaoh, as interpreted by Sayyid Quthb, illustrates Mu'min's ability to influence Pharaoh, who initially wanted to kill Prophet Moses, until Pharaoh finally abandoned his plan. This was achieved through the presentation of rational, ethical arguments that touched on psychological aspects. The focus of this study is Sayyid Quthb's interpretation of the dialogue, as well as examining the principles of communication contained therein. This research also identifies Quthb's line of thinking by looking at his ideological and socio-political background. Using qualitative methods and a literature study of Tafsir Fii Zhilalil Qur'an, the results of this study show that Quthb describes Mu'min as a communicator who is courageous, rational, and cares about the spirituality of his communication. This dialogue reflects three principles of effective communication: the moral courage to convey the truth, wisdom in choosing words and timing, and the ability to manage emotions so that the message touches the heart. The combination of historical, logical, and emotional arguments illustrates the harmony of ethos, pathos, and logos that is humanistic and persuasive. Quthb's thinking seems to have been greatly influenced by his life experiences under Egypt's authoritarian regime. Through the styles of al-Adabi wa al-Ijtima'i and da'wah harakah, he viewed this dialogue as a symbol of the resistance of truth against injustice, so that his interpretation was ideological, revolutionary, and anti-authoritarian.